Top-down analytical platforms for the characterization of the human salivary proteome. (February 2014) - Cabras, Tiziana; Iavarone, Federica; Manconi, Barbara; Olianas, Alessandra; Sanna, Maria Teresa; Castagnola, Massimo; Messana, Irene
Comprehensive analysis and characterization of the human salivary proteome is an important step towards the possible use of saliva for diagnostic and prognostic purposes. The contribution of the different sources to whole saliva, and the evaluation of individual variability and physiological modifications have been investigated by top-down proteomic approaches, disclosing the faceted and complex profile of the human salivary proteome. All this information is essential to develop saliva protein biomarkers. In this Review the major results obtained in the field by top-down platforms, and the improvements required to allow a more complete picture, will be discussed.